HUBUNGAN PENGETAHUAN IBU NIFAS TENTANG NUTRISI MASA NIFAS DENGAN PENYEMBUHAN LUKA PERINEUM DI DESA KESIMAN TENGAH KECAMATAN PACET KABUPATEN MOJOKERTOÂ - Yulianti, Indra; Khalimatus Saâ€™diya, Lida (JURNAL KEPERAWATAN BINA SEHAT, 2014)
In the post-partum period of high nutritional needs with sufficient calories, protein, fluid and vitamins. Nutrition is a major element in helping to repair cells, mainly because of the content of nutrients contained in it. The purpose of this research is to know the relation of mothers Knowledge about nutrition puerperium parturition with perineum wound healing. The study uses a kind of analytic korelasional research with cross sectional design. Independent variables and the dependent variable nutritional knowledge of wound healing. With a population of as many as 19 people. Number of samples 18 people using purposive sampling technique. Data collection using the observation sheet and questionnaire sheet. Based on the results of Spearman-rho statistical test using the SPSS software koefisian showed a correlation of 0.008> 0.05. Based on the results, 3 respondents (16.66%) have the knowledge of good and normal wound healing, as many as 5 respondents (27.77%) have sufficient knowledge of the normal wound healing respondents 3 and 2 respondents healing old wounds, as many as 10 respondents (55 , 55%) have less. knowledge of the normal wound healing respondents 2 and 8 respondents healing old wounds.The conclusion of this study indicate that the nutrition knowledge affect wound healing. It is therefore expected mother can eat foods with balanced nutrition is needed according to the puerperium.